Hierarchical Cu@MnO2 Core–shell Nanowires: A Nonprecious‐Metal Catalyst with an Excellent Catalytic Activity Toward the Reduction of 4‐Nitrophenol. Issue 18 (19th August 2016) - Du, Cheng; He, Shuijian; Gao, Xiaohui; Chen, Wei
Abstract: A nonprecious catalyst of hierarchical Cu@MnO2 core–shell nanowires was fabricated by a facile hydrothermal route and the nanostructured material showed a high catalytic activity toward the reduction of 4‐nitrophenol in the presence of NaBH4 . With an intact core–shell structure and porous MnO2 shell, the Cu@MnO2 nanowires exhibited an excellent catalytic activity with an activity factor of 571 s −1  g −1 and high recyclability with a conversion of 96 % after seven catalytic cycles. Abstract : Core–shell does well : A nonprecious catalyst of hierarchical Cu@MnO2 core–shell nanowires is fabricated by a facile hydrothermal route and the nanostructured material shows an excellent catalytic activity, as high as 571 s −1  g −1, toward the reduction of 4‐nitrophenol.